2016
DOI: 10.1007/s13595-016-0546-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the age-dependent changes in carbon stocks of Scots pine (Pinus sylvestris L.) stands in Turkey

Abstract: • Key message Simulated and observed carbon stocks in Scots pine forests varied considerably with stand age. The contribution of biomass to the total forest carbon stocks increased and that of dead organic matter decreased with increasing stand age. • Context Understanding changes in forest carbon stocks over time is important to estimate carbon inventory. Although Scots pine (Pinus sylvestris L.) is a main species in Turkey, studies on such changes are still lacking. • Aims We aimed to estimate the changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…Age is the most important factor affecting the magnitude and distribution of biomass in plantation ecosystems [13,42]. With increasing stand age, the total tree, aboveground, stem and root biomass of Mongolian pine increased, displaying a linear increase in this study (Figure 4).…”
Section: Biomass Distributionmentioning
confidence: 56%
“…Age is the most important factor affecting the magnitude and distribution of biomass in plantation ecosystems [13,42]. With increasing stand age, the total tree, aboveground, stem and root biomass of Mongolian pine increased, displaying a linear increase in this study (Figure 4).…”
Section: Biomass Distributionmentioning
confidence: 56%
“…Forest carbon pools generally vary with stand age [8,40,41]; however, in our study, we focused on the old-growth stands, specifically assessing the age range of 163-218 years. Our results showed that the forest carbon pools did not change significantly over the analysed period.…”
Section: Discussionmentioning
confidence: 99%
“…The FBDC model requires air temperature, species, and stand age as input data. This model has been applied to the temperate, tropical, and alpine regions in various developing countries (Yi et al 2013;Lee et al 2014Lee et al , 2016Lee et al , 2017Lee et al , 2018aLee et al , 2018b. The detailed description of the FBDC model can be found in the studies by Yi et al (2013) and Lee et al (2014).…”
Section: Structure Of the Forest C And N Modelmentioning
confidence: 99%